Clinical observation of Shenfu injection in treating patients with internal watershed cerebral infarction (参附注射液治疗内分水岭脑梗死临床观察) - YANG Junhang (杨俊行); LI Jie (李杰); HU Zhe (胡哲); FU Jingna (付景娜); FENG Huimin (冯慧敏) (中西医结合护理)
Objective To investigate the effect of Shenfu injection in treating patients with acute internal watershed cerebral infarction. Methods Totally 154 patients with AIWCI admitted to the Department of Encephalopathy of Dongzhimen Hospital from October 2018 to October 2020 were divided into the experimental group (n=96)and the control group(n=58). All cases received a comprehensive treatment including anti-platelet aggregation, lowering blood lipid, regulating blood pressure, replenishing blood volume, improving microcirculation and protecting brain cells. Patients in the experimental group were additionally given Shenfu injection for 14 days as a course of treatment. Before and after treatment, the National Institutes of Health Stroke Scale (NIHSS) was used to score the neurological impairment, and transcranial doppler (TCD) was used to measure the blood flow velocity of the middle cerebral artery at the affected side. Results The blood flow velocity of middle cerebral artery in 2 groups was increased after treatment, and the experimental group had a better improvement in Peak systolic velocity (Vs) and end-diastolic flow velocity (Vd) compare with the control group(P<0. 01). The NIHSS score of the experimental group was lower than that of the control group after treatment (P＜0. 05). The overall response rate in the experimental group was higher than that of the control group(P＜0. 05). Conclusion Shenfu injection can significantly improve the blood flow velocity of the distal artery responsible for internal watershed cerebral infarction caused by middle cerebral artery stenosis, and reduce the severity of neurologic impairment. (目的 探讨参附注射液治疗急性内分水岭脑梗死的效果。方法 选取2018年10月—2020年10月医院脑病科收治的急性内分水岭脑梗死患者154例, 分为试验组(n=96)和对照组(n=58)。2组均给予抗血小板聚集、降血脂、调控血压、补充血容量、改善微循环、保护脑细胞等治疗措施。试验组在此基础上加用参附注射液, 14 d为1个疗程。治疗前后应用卒中量表(NIHSS)进行神经功能缺损评分, 通过经颅多普勒(TCD)检测2组患者病变侧大脑中动脉血流速度。结果 与治疗前比较, 2组患者治疗后大脑中动脉血流速度均有提高, 试验组收缩期峰值流速(Vs)和舒张末期血流速度(Vd)指标改善幅度优于对照组, 差异有统计学意义(P＜0. 01)。治疗后试验组 NIHSS评分低于对照组, 差异有统计学意义(P＜0. 05)。试验组总有效率高于对照组, 差异有统计学意义(P＜0. 05)。结论 参附注射液治疗可明显改善大脑中动脉狭窄所致内分水岭脑梗死责任动脉远端的血流速度, 减轻患者神经功能缺损程度。)